Media Pembelajaran Interaktif Budaya Melayu Riau berbasis WebGL - Rivaldo Famren Silaen; Wilda Susanti; Gusrio Tendra; Yenny Desnelita; Gustientiedina Gustientiedina (Universitas Hamzanwadi, 2023)
Currently, people in Riau province, children and adults, lack knowledge about Riau Malay culture, about traditional costumes, traditional dances, traditional houses, and traditional weapons. The introduction of Malay Riau culture into preschool has not been done properly, has not been integrated into the school curriculum, and existing media are still limited in expressing 2D images. The purpose of this study is to create interactive learning materials using web-based WebGL technology in order to help children get to know Riau Malay culture. This research uses the waterfall approach, which consists of needs analysis, system design, implementation or code writing, and system testing using the Black Box System. Data collection techniques by making observations at the Sang Nila Utama Museum. The result of this study is a learning medium to help early childhood learners get to know Riau Malay culture. The test results showed that all functional systems worked well, and this learning medium was accepted by all 7 respondents with a satisfaction level of 87.6% through user acceptance. Based on the test results and the level of respondent satisfaction, it was concluded that this system can be accepted by many users, and it is expected that this system can be integrated with the existing curriculum.